REVIEW OF SOME CRIMINAL JUDGMENTS THAT DO NOT RESOLVE THE SUBSTANCE OF THE CASE - PROCEDURAL MEAN TO ENSURE THE LEGAL ORDER - Lorincz, Anca-Lelia (International Journal of Legal and Social Order, 2025)
Among the meanings of the concept of "legal security" is the feeling of confidence of citizens in the correct application and interpretation of the law, as well as in the state's ability to ensure the legal order and, implicitly, public order. One of the requirements arising from the principle of security of legal relations is ensuring access to justice by guaranteeing the right to an effective remedy. In this context, the present study approaches the institution of revision, bringing into attention the possibility of subjecting to re-examination, by exercising this way of attack, definitive criminal judgments that do not resolve the merits of the case. Using, as research methods, observation, documentation, interpretation and comparative scientific analysis (including some European provisions), this paper also discusses some jurisprudential aspects regarding criminal judgments that can be subject to revision, with reference to the recent practice of the supreme court (High Court of Cassation and Justice) in Romania. The objective of the study is to highlight the need to correlate the requirement of ensuring the stability of final criminal judgments with the requirement of guaranteeing access to justice by exercising an effective remedy.